Colours of the sky - popular meteorology in Portuguese proverbs - Padala, Zyta (Romanica Olomucensia, 2015)
The aim of this article is to study Portuguese meteorological proverbs in which the weather forecast is based on an observation of the colours of the sky. The creation of meteorological proverbs results from an attempt to predict the weather circumstances that condition various aspects of human life, in particular the daily activities of farm workers and sailors, which are both common occupations in Portugal. The proverbs that are analysed reflect the thoughts and beliefs of the Portuguese nation. By merging folk legends and superstitions with observed facts, Portuguese people created a series of meteorological proverbs in which an observable change in the colour of the sky forewarns of the forthcoming alteration of the weather conditions.
Keywords: colours; paremiology; popular meteorology; Portuguese culture; proverbs.